Intestinal Serum amyloid A suppresses systemic neutrophil activation and bactericidal activity in response to microbiota colonization - Murdoch, Caitlin C.; Espenschied, Scott T.; Matty, Molly A.; Mueller, Olaf; Tobin, David M.; Rawls, John F. (PLOS Pathogens, 2019)
Author summary The intestine is colonized by complex microbial communities called the microbiota, which impacts diverse aspects of host physiology including development and function of the innate immune system. Neutrophils are phagocytic innate immune cells essential for host defense against infection. Neutrophil activity is strongly impacted by the microbiota but underlying mechanisms remain poorly defined. Here we show the evolutionarily-conserved secreted host protein Serum amyloid A (Saa) mediates microbiota-dependent effects on systemic neutrophil function. Saa is produced by the intestine and liver in response to the microbiota, but its in vivo functions have remained elusive. Using zebrafish, we demonstrate that Saa promotes neutrophil recruitment to peripheral injury yet restricts clearance of pathogenic bacterial infection. Analysis of isolated neutrophils revealed Saa reduces bactericidal activity and expression of pro-inflammatory genes in a microbiota-dependent manner. Transgenic expression of saa in the intestine and liver of saa mutants was sufficient to rescue mutant phenotypes, and intestinally-derived saa also alleviated defects in neutrophil recruitment to peripheral injury in germ-free zebrafish. Collectively, these data establish that Saa induced by the microbiota in the intestine signals systemically to neutrophils, tuning the extent to which they may be activated by other microbes or respond to injury.